Lonely Champions in Japanese Panels: Deconstruction of Violent Success in Male Representations on seinen Manga - Martínez Alcaide, Fabio; Lima de Carvalho, Milena Carla; Rubira García, Rainer (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Although Japanese manga aimed at male demographics has always designed its main characters according to the archetypes of the patriarchal tradition, there are several works that manage to break away from this discursive trend. Instead of perpetuating the system of confrontations that structures the plot of most of the fictions of the genre, these series choose to present violent and triumphant characters but deeply dissatisfied with their vital condition. This text intends to make a critical analysis of the implicit discourse in the deconstruction exercise they put into practice and to identify the most characteristic attributes of their characters, based on the case study of three series representative of the trend.